The acceptability of using IUDs among Egyptian nulliparous women: a cross-sectional study - Reham Refaat Elkhateeb; Eman Kishk; Ahmad Sanad; Haitham Bahaa; Abdel Rahman Hagazy; Kareem Shaheen; Enas Moustafa; Hahem Fares; Khalid Gomaa; Ahmad Mahran (BMC, 2020)
Abstract Background Although intrauterine contraceptive device is highly effective, safe, long term and reversible method of contraception, the general population and physicians refuse. IUDs for nulliparous women due to persistent rumors about its side effects and complications. The aim of this study was to assess the acceptability of IUD use in nulliparous women by both women and health care providers in Egypt. Methods Five hundred thirty nulliparous women and 200 physicians were interviewed in 10 family planning clinics in Suez and Minia cities - Egypt. The knowledge and attitudes of women and health care providers towards IUD use in nulliparous women were assessed through a well designed questionnaire over 2 years. Those women who accepted using IUD were then followed up for 6 months. Results Most of nulliparous women sought for contraception reported a negative impression of IUD method (96.2%). 82.5% of physicians had the same attitude. The reasons for refusing IUD among nulliparous women are fear of side effects including infection (52.8%), and bleeding (37.7%).Also, fear of subsequent infertility 51.9% of women. Regarding the providers, increased pelvic inflammatory disease (PID) represented the highest percentage (70%) for non acceptability, followed by difficult insertion (52.5%). Ninety women who accepted use IUD were followed up 6 months later, 94.4% were still using the method and77.8% were happy with the results. Conclusion The main barriers that hinder the use of IUD in nulliparous women are the women insufficient knowledge and attitude of their physicians. Good client counseling. Good training for physician to improve their experience would help increase the use of such effective and safe method.